Mycobacterial PPE36 Modulates Host Inflammation by Promoting E3 Ligase Smurf1-Mediated MyD88 Degradation - Peng, Zhangli; Yue, Yan; Xiong, Sidong (Frontiers in Immunology, 2022)
Mycobacterium tuberculosis (Mtb) PPE36, a cell-wall-associated protein, is highly specific and conserved for the Mtb complex group. Although PPE36 has been proven essential for iron utilization, little is known about it in regulating host immune responses. Here we exhibited that PPE36 was preferentially enriched in Mtb virulent strains and could efficiently inhibit host inflammatory responses and increase bacterial loads in infected macrophages and mice. In exploring the underlying mechanisms, we found that PPE36 could robustly inhibit the activation of inflammatory NF-κB and MAPK (Erk, p38, and Jnk) pathways by promoting E3 ligase Smurf1-mediated ubiquitination and proteasomal degradation of MyD88 protein. Our research revealed a previously unknown function of PPE36 on modulating host immune responses and provided some clues to the development of novel tuberculosis treatment strategies based on immune regulation.